Fourth‐generation glucose sensors composed of copper nanostructures for diabetes management: A critical review. Issue 1 (9th September 2021) - Naikoo, Gowhar A.; Awan, Tasbiha; Salim, Hiba; Arshad, Fareeha; Hassan, Israr U.; Pedram, Mona Zamani; Ahmed, Waqar; Faruck, Hakkim L.; Aljabali, Alaa A. A.; Mishra, Vijay; Serrano‐Aroca, Ángel; Goyal, Rohit; et al.
Abstract: More than five decades have been invested in understanding glucose biosensors. Yet, this immensely versatile field has continued to gain attention from the scientific world to better understand and diagnose diabetes. However, such extensive work done to improve glucose sensing devices has still not yielded desirable results. Drawbacks like the necessity of the invasive finger‐pricking step and the lack of optimization of diagnostic interventions still need to be considered to improve the testing process of diabetic patients. To upgrade the glucose‐sensing devices and reduce the number of intermediary steps during glucose measurement, fourth‐generation glucose sensors (FGGS) have been introduced. These sensors, made using robust electrocatalytic copper nanostructures, improve diagnostic efficiency and cost‐effectiveness. This review aims to present the essential scientific progress in copper nanostructure‐based FGGS in the past 10 years (2010 to present). After a short introduction, we presented the working principles of these sensors. We then highlighted the importance of copper nanostructures as advanced electrode materials to develop reliable real‐time FGGS. Finally, we cover the advantages, shortcomings, and prospects for developing highly sensitive, stable, and specific FGGS.